Exclusivity clauses: Enhancing competition, raising prices - Marc Blatter; Silvio Sticher (University of Bern, Department of Economics, 2013)
In a setting where retailers and suppliers compete for each other by offering binding contracts, exclusivity clauses serve as a competitive device. As a result of these clauses, firms addressed by contracts only accept the most favorable deal. Thus the contract-issuing parties have to squeeze their final customers and transfer the surplus within the vertical supply chain. We elaborate to what extent the resulting allocation depends on the sequence of play and discuss the implications of a ban on exclusivity clauses.
Keywords: D86; L13; L42; 330; exclusive dealing; exclusive provision